Internet-based technique and social support in the management of depression among secondary school teachers in Oyo State, Nigeria - Olanrewaju, Muraina Kamilu; Olabisi, Oladimeji Lateefah (Universitas Ahmad Dahlan, 2022)
Depression represents one of the major health concerns in the recent time and affects deeply individuals, families and has tremendous effects for the society. This study therefore examined the internet-based technique and social support in the management of depression among secondary school teachers in Oyo State, Nigeria. Pretest-posttest, control group quasi-experimental design with a 2 x 2 factorial matrix was used in the study. Simple random sampling technique was used in sampling 77 participants from 4 local government area in Oyo State, Nigeria. The respondents were measured with validated instrument of .95 and the data obtained was analyzed using t-test statistical analysis. Two research hypotheses were formulated and tested at 0.05 level of significance. The result showed that there was significant difference in the depression of secondary school teachers exposed to internet-based technique and those in the control group (t = 76.91; p < 0.05) and there was significant difference in the depression of secondary school teachers with high social support and those with low social support (t = 37.82; p < 0.05). In view of these findings, the study recommended that educational stakeholders should intensify their effort to organize conferences on the implications of internet-based technique and social support as effective interventions towards managing the depression and that curriculum planner should try as much as possible to include in the scheme of teacher training, skills on internet-based technique.